Non-Institutional Punishment Model in Child Sexual Violence Cases: An Analysis of The Progressiveness of Restorative Justice Towards Repetition of Criminal Acts - Zerlina Chaira Rani; Hanifah Febriani (Proceeding International Conference Restructuring and Transforming Law, 2026)
This study examines the legal issues in the criminalization of sexual violence crimes involving children as perpetrators and victims. The main objective of the study is to analyze the legal considerations of the panel of judges in Decision Number 2/Pid.Sus-Anak/2024/PN Skt and to identify the criminalization model for child perpetrators of sexual violence in the Indonesian criminal justice system. The research method used is normative juridical with a descriptive analytical approach through the study of legal documents. The results show that the Surakarta District Court Judge applied the doctrine of statutory rape by affirming that the child victim's consent was legally invalid due to legal incompetence and psychological manipulation, the panel of judges sentenced him to 10 months in prison with a one-year probation period and three months of job training. This decision represents a paradigm shift from retributive justice (imprisonment) to restorative justice, which prioritizes the principle of last resort. The research conclusion confirms that the non-institutional punishment model aims to prevent stigmatization and recidivism among child perpetrators, although on the other hand, it triggers challenges related to disparities in sentencing and fulfilling a sense of justice for victims.